Dukungan Keluarga Pada Pasien Diabetes Melitus Tipe 2 di Puskesmas Pare Kabupaten Kediri - Pria Wahyu Romadhon Girianto (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2023)
The development of the era and the increasingly sophisticated media have an impact on shifting patterns of human behavior that change between living a healthy life and consuming fast food. Diabetes mellitus is a chronic metabolic disorder that requires a long-term treatment process so that people with Diabetes Mellitus can cause stress. In order to be able to adjust to the conditions of the disease experienced, it is necessary to have family support, which is very necessary for the treatment process for sufferers. Family support can be in the form of emotional support, appreciation support, instrumental support, or informational support. The purpose of this study was to determine family support for patients with Type 2 Diabetes Mellitus at the Pare Health Center, Kediri Regency. The research design used was descriptive with a sample of 33 respondents, and the sampling technique was accidental sampling. The analysis used is a descriptive statistical test. The results showed that most of the respondents with Type 2 Diabetes Mellitus had good family support (51.5%). It is hoped that the family will always provide the facilities needed by the patient, and it is hoped that the family will be able to play an active role in supporting Type 2 Diabetes Mellitus patients during the treatment period.